Genome‐wide mapping of plasma protein QTLs identifies putatively causal genes and pathways for cardiovascular disease - Chen Yao (Nature Portfolio, 2018)
Genetic variation can influence levels of disease-related plasma proteins and, thus, contribute to the pathogenesis of complex diseases. Here, the authors perform genome-wide QTL analysis for 71 plasma proteins to identify causal proteins for coronary heart disease and provide a molecular QTL browser.